Correlated seasonal dyskalaemia in a primary care population: winter hyperkalaemia and summer hypokalaemia - Amro Maarouf; Jordan Danks; Jonathan Fenn; Rousseau Gama; Tejas Kalaria (Clinical Chemistry and Laboratory Medicine (CCLM), 2026)
Abstract Objectives In vitro serum potassium is affected by ambient temperature with peaks in the winter and troughs in the summer. We investigated whether primary care phlebotomy locations with higher winter hyperkalaemia rates exhibited higher summer hypokalaemia and evaluated a simple screening metric to identify high-risk locations. Methods Retrospective audit of Indexor-tracked primary care potassium results analysed at a UK hub laboratory between 1 July 2024 and 30 June 2025 was performed. Bivariate multilevel logistic regression modelling assessed whether locations with higher hyperkalaemia rates in January 2025 (coldest month) also showed higher hypokalaemia rates in June 2025 (warmest month). Locations were ranked by January hyperkalaemia frequency and analysed by quartiles. ROC analysis assessed the performance of ΔK (difference in winter and summer mean potassium) in identifying highest seasonal dyskalaemia locations. Results Among 382,735 included results, serum potassium was inversely associated with ambient temperature. Hyperkalaemia was 5.24 % in January 2025 vs. 0.90 % in June 2025, while hypokalaemia was 0.39 % vs. 2.22 %, respectively. Location-level propensities for January hyperkalaemia and June hypokalaemia correlated positively (ρ=0.35; 95 % CrI 0.02–0.62). The highest-risk quartile locations had greater winter hyperkalaemia (11.44 % vs. 2.97 %; OR 4.22) and summer hypokalaemia (3.12 % vs. 1.51 %; OR 2.10) compared with the lowest quartile. ΔK discriminated top-quartile risk locations (AUC 0.918 for winter hyperkalaemia), with an optimal threshold ΔK≈0.40 mmol/L. Conclusions Phlebotomy locations prone to winter hyperkalaemia also exhibit summer hypokalaemia, reflecting location-specific pre-analytical vulnerabilities. A simple ΔK screen can help targeted mitigation for seasonal dyskalaemia such as on-site centrifugation or transport optimisation.